A two-step method for fabricating large-area textile-embedded elastomers for tunable friction. Issue 10 (31st October 2018) - Ohzono, Takuya; Teraoka, Kay
Abstract : Recently, shape-tunable wrinkles formed on an elastomeric sheet with a textile finely embedded in proximity to the surface have been developed for in situ control of friction depending on various situations. For their actual uses, sheets with a large area are desired. A key challenge on their fabrication is to overcome the non-uniformity of the vertical position of the textile embedded within the elastomeric sheet, which causes substantial reduction in the tunable range of friction. The defect originates from the increased difficulty, as the sheet area is scaled up, of squeezing a viscoelastic precursor liquid due to the use of a deformable elastomeric surface. Here, we report a new two-step method for a textile-embedded elastomeric sheet that avoids using the soft elastomeric surface on the squeezing process and requires post-joining to an elastomeric base sheet. The obtained sheet with a large area (180 × 180 mm), was uniform and showed a large change of friction on its strain-induced transformation between flat and wrinkled states. The relationship between the experimentally controllable parameters and the squeeze film hydrodynamics is theoretically discussed, which is generally applicable to precise embedding micro-objects at the elastomer surface.